Problems of the elimination of criminal sanctions in law number 2 of 2017 concerning construction services: A study of policies and legal protection of construction accident victims - Ismaidar Ismaidar; Bambang Fitrianto; Haris Habibi; Sagita Purnomo; Enda Leginta Barus; Bima Lumbanbatu (Priviet Social Sciences Journal, 2025)
The abolition of criminal sanctions in Law Number 2 of 2017 concerning Construction Services creates a vacuum and uncertainty in law enforcement. Previously, in cases of construction failures and accidents that caused injuries and deaths, the perpetrators could be charged with Article 43 of Law Number 18 of 1999 concerning Construction Services, but with the removal of this criminal provision, law enforcement was carried out using the Criminal Code and/or building law. This condition results in disparities in the law enforcement. This research aims to discuss the void of criminal law in Law Number 2 of 2017 concerning Construction Services and comprehensively examine policies and legal protection for construction accident victims. The type of research used is normative juridical with a descriptive-analytical approach, discussing existing legal symptoms and problems and testing them based on applicable laws and regulations. The results of this study show that the void in criminal law in construction services law occurs due to the elimination of criminal sanctions based on legal political factors; thus, law enforcement for construction accidents cannot be carried out using special laws on construction services. Legal protection for victims of construction accidents is emphasized in law enforcement to provide a deterrent effect against perpetrators, consisting of the application of strict sanctions, compensation for victims, and the implementation of occupational health and safety management standards.